2007
DOI: 10.4283/jmag.2007.12.2.068
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Structures and Magnetism in Iron: Ferromagnetism and Antiferromagnetism

Abstract: Even a pure bulk Fe has a complicated magnetic phase and its magnetism is still needed to be clarified. In this study we investigated the magnetism of bcc and fcc bulk Fe with total energy calculations as functions of atomic volume. The full-potential linearized augmented plane wave method was adopted within a generalized gradient approximation. The ground state of bulk Fe is confirmed to be of ferromagnetic (FM) bcc. For fcc structured Fe an antiferromagnetic (AFM) state is more stable compared to FM states w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Following the "Jacob's ladder" of the XC functional, introduced by Perdew [3], the second rung above the LDA was implemented by introducing gradient corrections, which led to the generalized gradient approximation (GGA) [4,5]. This gradient correction approach has resulted in considerably better agreement between experiment and theory for the basic properties of transition metals [6][7][8][9][10][11][12][13][14]. For instance, the GGA provides the correct results for the ferromagnetic (FM) bcc ground state for Fe, while the ground state of the LDA is the nonmagnetic (NM) hcp phase [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the "Jacob's ladder" of the XC functional, introduced by Perdew [3], the second rung above the LDA was implemented by introducing gradient corrections, which led to the generalized gradient approximation (GGA) [4,5]. This gradient correction approach has resulted in considerably better agreement between experiment and theory for the basic properties of transition metals [6][7][8][9][10][11][12][13][14]. For instance, the GGA provides the correct results for the ferromagnetic (FM) bcc ground state for Fe, while the ground state of the LDA is the nonmagnetic (NM) hcp phase [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This gradient correction approach has resulted in considerably better agreement between experiment and theory for the basic properties of transition metals [6][7][8][9][10][11][12][13][14]. For instance, the GGA provides the correct results for the ferromagnetic (FM) bcc ground state for Fe, while the ground state of the LDA is the nonmagnetic (NM) hcp phase [10][11][12]. However, the LDA or GGA based on the DFT fails in the description of band gaps of semiconductors and insulators [15].…”
Section: Introductionmentioning
confidence: 99%
“…The representa-a͒ Author to whom correspondence should be addressed. 4,5,9,11 The results of vibrating sample magnetometer measurements at room temperature show the typical paramagnetic properties. Tel.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic studies based on first-principles calculations have been reported on the relationship between the magnetic moment and volume expansion of iron [27][28][29]. All of these calculations assume uniform volume expansion.…”
Section: Discussionmentioning
confidence: 99%